ke, ber, me, the STUDI KOMPARATIF STRATEGI INFLUENCER MARKETING, PEMANFAATAN MEDIA SOSIAL DAN VARIAN PRODUK DALAM UPAYA MENINGKATKAN JUMLAH CUSTOMER : (Studi Kasus Bakso Pelakor Dan Bakso Bengkong Di Kec. Klampis Kab.Bangkalan) - yana, muzayyanah; Aulia Dawam (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This research aims to analyze the comparison of influencer marketing strategies, the utilization of social media, and product variations in increasing customer numbers at Bakso Pelakor and Bakso Bengkong in Klampis District, Bangkalan Regency. The methodology used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results show that Bakso Pelakor relies on influencers to expand market reach and enhance credibility, while Bakso Bengkong focuses on organic content and product authenticity. Although Bakso Pelakor successfully attracts attention with menu innovations and aggressive promotions on social media, Bakso Bengkong maintains loyal customers through taste quality and service. These findings indicate that both businesses have different approaches in their marketing strategies, which affect consumer perceptions and purchasing decisions. This research is expected to provide insights for SMEs in developing more effective marketing strategies in the digital era.